1995
DOI: 10.1093/nar/23.23.4777
|View full text |Cite
|
Sign up to set email alerts
|

Control of HPV 18 DNA replication by cellular and viral transcription factors

Abstract: Papillomavirus replication in vivo requires the interaction of the virally encoded proteins El and E2 with the origin of replication which is localised in the regulatory region (long control region or LCR) of the viral genome. In genital human papillomaviruses (HPVs), the origin overlaps promoter elements of early transcription. In this study, we analysed the replication of HPV18 DNA using the complete LCR containing mutations in transcription regulatory elements. We found that each of the three E2 binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 50 publications
1
53
1
Order By: Relevance
“…For replication experiments an E1 expression plasmid was constructed from the originally described E1/E2 expression plasmid EapCG (Demeret et al, 1995) by inserting a TTL (Translation Termination Linker) in the restriction sites SexA1 in the E2 ORF, and Blp1 in the E7 ORF. The origin-containing plasmid, poril8, was described in (Demeret et al, 1995).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For replication experiments an E1 expression plasmid was constructed from the originally described E1/E2 expression plasmid EapCG (Demeret et al, 1995) by inserting a TTL (Translation Termination Linker) in the restriction sites SexA1 in the E2 ORF, and Blp1 in the E7 ORF. The origin-containing plasmid, poril8, was described in (Demeret et al, 1995).…”
Section: Plasmidsmentioning
confidence: 99%
“…Replication assays were performed as previously described in (Demeret et al, 1995). Brie¯y, 2 mg of the pori18 plasmid were cotransfected with 2 mg of the E1 expression plasmid and 1 mg of plasmids expressing either wt or mutant E2 proteins in 293 cells.…”
Section: Replication Assaysmentioning
confidence: 99%
“…In the case of papillomavirus a viral helicase, E1 (67), in concert with a viral auxiliary protein, E2, unwinds the viral origin of replication and initiates DNA synthesis (13,17,18,62). However, long-term maintenance of a viral oriP-con- FIG.…”
mentioning
confidence: 99%
“…In an extension of this work presented here, the functional significance of two naturally occurring mutations in the Sp1 site proximal to the HPV-18 E6\E7 promoter was assessed. Sp1 is a key activator of RNA polymerase II dependent promoters in HPV (HoppeSeyler & Butz, 1992) as in other systems (Kadonga et al, 1986), and has been recently identified as an accessory element in papillomavirus replication (Demeret et al, 1995).…”
mentioning
confidence: 99%
“…The viral E2 protein plays an important role in promoter repression, through binding to its two recognition sites (BS1 and BS2) in the promoter proximal region of the HPV-18 URR (Steger & Corbach, 1997). The binding of E2 protein to these sites has been shown in vitro to interfere with the binding of Sp1 to its cognate sequence lying nearby (Demeret et al, 1995). This suggests that stronger binding of Sp1 may decrease the ability of the E2 protein to repress promoter activity.…”
mentioning
confidence: 99%